Profitabilitas, Likuiditas, Kepemilikan Pemerintah dan Kualitas Pengungkapan Corporate Social Responsibility - Rondonuwu, Jordan Rudolf Daniel; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p02, 2024)
The energy sector, being environmentally sensitive, often exhibits low-quality disclosure of corporate social responsibility (CSR). This study aimed to ascertain the relationship between profitability, liquidity, and government ownership on the quality of CSR disclosure among energy sector companies listed on the IDX. Out of a research population of 64 energy sector companies, 51 were selected for observation. Data collected was subsequently analyzed using multiple linear regression for panel data with the STATA 17 tool. Results indicated that while profitability positively correlates with the quality of CSR disclosure, liquidity and government ownership do not significantly impact the quality of such disclosures.